Selection and evaluation of Azospirillum brasilense strains growing at a sub-optimum temperature in rhizocoenosis with wheat - Kaushik, R; Saxena, A K; Tilak, K V (Folia microbiologica, 2001)
Fourteen Azospirillum brasilense strains growing at a sub-optimum temperature were selected based on their ability to grow and carry out plant growth promoting activities at 22 degrees C. The strains were tested for their response to inoculation in wheat (two popular cultivars, HD2285 and WH547, under sterile conditions) crop using sterile and nonsterile rooting medium. Significant increase in plant growth parameters was observed; the overall response to inoculation was better in cultivar HD2285. Based on their performance under sterile conditions, 4 strains were selected and compared under nonsterile conditions with strain sensitive to a sub-optimum temperature in pots using wheat variety HD2285. The strains capable of growing at the sub-optimum temperature can colonize the wheat endorhizosphere efficiently and improve the plant growth and yield as compared to sensitive strain; a 25-27% increase in grain yield was found on inoculating two selected strains compared to NO3- control.
Keywords: Soil Microbiology; Nitrogenase; kyseliny indoloctové; Indoleacetic Acids; regulátory růstu rostlin; pšenice; Azospirillum brasilense; Plant Roots; kořeny rostlin; Siderophores; půdní mikrobiologie; Temperature; siderofory; kultivační média; Triticum; Plant Growth Regulators; teplota; nitrogenasa; Culture Media